Isomorphism conditions for Cayley digraphs of different completely simple semigroups - John Meksawang (2018)
© 2015 Academic Publications, Ltd. The isomorphism problem for Cayley digraphs has been extensively investigated over the past 30 years. This paper we introduce the conditions for Cayley digraphs of different finite groups and of different completely simple semigroups can be isomorphic.